A picture to remember - Scott-Malden, Sarah (Cambridge English readers. Level 2, 1999)
Cristina Rinaldi works for the Museo Nacional de Bellas Artes in Buenos Aires. She loves art and is happy with her life. Then one day she has a motorbike accident and can't remember some things. But there are two men who think she remembers too much, and they want to kill her before she tells the police what she saw.